"Are you doing your pelvic floor?" An ethnographic exploration of the interaction between women and midwives about pelvic floor muscle exercises (PFME) during pregnancy. (April 2020) - Terry, Rohini; Jarvie, Rachel; Hay-Smith, Jean; Salmon, Victoria; Pearson, Mark; Boddy, Kate; MacArthur, Christine; Dean, Sarah
Abstract: Objective: Many women experience urinary incontinence (UI) during and after pregnancy. Pelvic floor muscle exercises (PFME) can prevent and reduce the symptoms of UI. The objective of the study was to explore challenges, opportunities and concerns for women and health care professionals (HCPs), related to the implementation of PFME training for women in current antenatal care. Design: An ethnographic study design was used. Researchers also formed and collaborated with a public advisory group, consisting of seven women with recent experiences of pregnancy, throughout the study. Participants: Seventeen midwife-woman interactions were observed in antenatal clinics. In addition, 23 midwives and 15 pregnant women were interviewed. Repeat interviews were carried out with 12 of the women postnatally. Interviews were also carried out with other HCPs; four physiotherapists, a linkworker/translator and two consultant obstetricians. Additional data sources included field notes, photographs, leaflets, policy and other relevant documents. Setting: Data were collected in three geographical areas of the UK spanning rural, urban and suburban areas. Data collection took place in antenatal clinics, in primary and secondary care settings, and the majority of women were interviewed in their homes. Findings: Three broad and inter-related themes of "ideological commitment", "confidence" and "assumptions, stigma and normalisation" were identified. The challenges, opportunities and concerns regarding PFME implementation were explored within these themes. Conclusions and implications for practice: Although HCPs and some women knew that PFME were important, they were not prioritised and the significant benefits of doing PFME may not have been communicated by midwives or recognised by women. There was a lack of confidence amongst midwives to teach PFME and manage UI within the antenatal care pathway and amongst women to ask about PFME or UI. A perceived lack of consistent guidelines and policy at local and national levels may have impeded clear communication and prioritisation of PFME. Furthermore, assumptions made by both women and midwives, for example, women regarding UI as a normal outcome of pregnancy, or midwives' perception that certain women were more likely to do PFME, may have exacerbated this situation. Training for midwives to help women in the antenatal period to engage in PFME could address challenges and concerns and to help prevent opportunities for women to learn about PFME from being missed.